Children's resilience to sibling victimization: The role of family, peer, school, and neighborhood factors - Sellars, Elise (Cambridge University Press, 2025)
Although common, little is known about the potential impacts of sibling victimization, and how best to ameliorate these. We explored longitudinal associations between sibling victimization and mental health and wellbeing outcomes, and promotive and risk factors that predicted better or worse outcomes following victimization. Data were from >12,000 participants in the Millennium Cohort Study, a longitudinal UK birth cohort, who reported on sibling victimization at age 11 and/or 14 years. We identified potential risk and promotive factors at family, peer, school, and neighborhood levels from age 14 data. Mental health and wellbeing outcomes (internalizing and externalizing problems, mental wellbeing, self-harm) were collected at age 17. Results suggested that over and above pre-existing individual and family level vulnerabilities, experiencing sibling victimization was associated with significantly worse mental health and wellbeing. Having no close friends was a risk factor for worse-than-expected outcomes following victimization. Higher levels of school motivation and engagement was a promotive factor for better-than-expected outcomes. This indicates that aspects of the school environment may offer both risk and promotive factors for children experiencing sibling victimization at home. We argue that effective sibling victimization interventions should be extended to include a focus on factors at the school level.